Tweeting links to Cochrane Schizophrenia Group reviews: a randomised controlled trial - Adams, Clive E.; Jayaram, M.; Bodart, A.Y.M.; Sampson, S.; Zhao, S.; Montgomery, Alan A. (BMJ Publishing Group Ltd, 2016)
Objective: To assess the effects of using health social media on web activity.